2021
DOI: 10.1111/ijcp.14153
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width in patients undergoing transcatheter aortic valve implantation: Implications for outcomes

Abstract: Background Red cell distribution width (RDW) is recently emerging as a prognostic indicator in many cardiovascular diseases. However, less is known about its predictive role in patients undergoing transcatheter aortic valve implantation (TAVI). Methods We retrospectively included very high‐risk patients with severe aortic valve stenosis undergoing TAVI between February 2012 and December 2019. Patients were classified according to RDW tertiles. Our primary endpoint was long‐term all‐cause mortality. The seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Reference range typically spans between 12-15% for RDW-CV (RDW reported as a coefficient of variation) [1]. Elevated RDW has been shown to predict adverse outcomes in selected cohorts of patients with specific cardiovascular diseases [2] such as acute coronary syndromes [3][4][5][6], heart failure [7], and atrial fibrillation [8][9][10]. The mechanism underlying this phenomenon is not entirely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Reference range typically spans between 12-15% for RDW-CV (RDW reported as a coefficient of variation) [1]. Elevated RDW has been shown to predict adverse outcomes in selected cohorts of patients with specific cardiovascular diseases [2] such as acute coronary syndromes [3][4][5][6], heart failure [7], and atrial fibrillation [8][9][10]. The mechanism underlying this phenomenon is not entirely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Valenti et al also reported that each percent increase in RDW is associated with 11% higher mortality in patients who had TAVI. 116 In a recent study by Marzec et al it was concluded that RDW is an independent predictor of mortality following TAVI. 117 Regardless of outcomes, a systematic review and meta-analysis had indicated that preprocedural higher RDW is associated with a higher risk of contrast-induced nephropathy.…”
Section: Atherosclerotic Disordersmentioning
confidence: 96%